Signs of the hour for the theologians and the people of hadith and the impact through inference from the hadiths of the nine books - Al Benna, Ahmed ben saad (Journal of Islamic Sciences, 2021)
The issues of the Last Day are among the great doctrinal issues and are the basis of the fifth pillar of faith in God Almighty. The signs of the Hour are the first issues of the Last Day, so they are worthy of research and contemplation. This is because the occurrence of some of these great signs heralds the change of events in the earthly and heavenly worlds. Therefore, knowing the correct approach based on taking evidence from the Qur’an and Sunnah and deducing the righteous predecessors of the nation is a topic worthy of research and care. As the signs of the Hour are closely related to the Islamic faith Hence this research, which came to clarify the position of the Mu’tazilites regarding the signs of the Hour, with a statement of the methodology of the Sunnis and the group, and I tried to be the scope and nature of the research through what each team inferred on this issue from the hadiths of the nine books, with a discussion of those sayings, and a statement of the correctness In it, concluding with the most important results that I reached from this research, which I ask God to be of benefit and benefit to the writer and the reader, he is the guardian of that and the capable of it, and praise be to God, Lord of the Worlds, and prayers and peace be upon our Prophet Muhammad and all his family and companions.